Veterinary and animal ethics : proceedings of the First International Conference on Veterinary and Animal Ethics, September 2011 - Wathes, Christopher M. (Wiley-Blackwell, 2012)
The first International Conference on Veterinary and Animal Ethics (ICVAE) held in September 2011 saw leading experts from across the world come together to discuss the most important issues of animal welfare in contemporary veterinary practice and research. This is the extended proceedings of that conference, enabling all those interested in this increasingly significant subject to benefit from the insights of those discussions. The conference was divided into four sessions: Principles of veterinary and animal ethics; Justifying ends - the morality of animal use; Ethical analyses of.